VD_FINDINFO HC / 2012 / 769 vom 26. Oktober 2012 - VD Tribunal cantonal (2012)
RÉPARTITION DES FRAIS, FRAIS JUDICIAIRES, DÉPENS, RETRAITVOIE DE DROIT | 106 al. 1 CPC (CH), 107 al. 1 let. e CPC (CH), 110 CPC (CH)